PTH-135 Patients' perceptions of constipation differ strikingly from those of both general practitioners and gastroenterology specialists, and there is no consistent agreement with the rome iv criteria. (17th June 2017) - Dimidi, E; Hovanov, A; Cox, C; Neville, S; Grant, R; Scott, SM; Whelan, K
Abstract : Introduction: Although constipation is a prevalent condition, it is unclear whether patients' and doctors' perceptions of the definition of constipation agree with each other or with formal diagnostic criteria. Method: A survey was conducted to compare the perceptions of constipation diagnosis within the adult general population (with and without constipation), gastroenterology specialists (gastroenterologists, coloproctologists) and General Practitioners (GPs). Symptoms considered important in diagnosing constipation, together with 10 case studies based on the Rome IV criteria were investigated. Results: 2257 members of the general population (1623 self-reported constipation, 934 without), 365 gastroenterology specialists and 411 GPs completed the survey. Only a minority of the general population considered the Rome IV symptoms important for diagnosing constipation (Table 1). Infrequent bowel movements were most frequently reported as important by GI specialists (65%), compared with less than half of GPs (41%) and less than a third of the constipated general population (26%) (p<0.001). The symptom most frequently reported as important for diagnosing constipation by the general population was straining (40%–43%). In the 10 case studies, correct diagnoses were made by doctors (GPs and GI specialists) on 79%–80% of occasions. However, on average, the absence of constipation was correctly identified by doctors in 85%–92% of the cases without constipation, whereas the presence of constipation was correctly identified in only 60%–70% of the cases with constipation. Conclusion: There are striking differences in the symptoms consistent with constipation between the general population, gastroenterology specialists and GPs, and variable agreement with the Rome IV criteria. These differences have major implications for patient care and satisfaction with treatment. The findings reinforce the need to re-evaluate current diagnostic criteria for constipation and to ensure these are communicated widely. Disclosure of Interest: None Declared